Haiza lighting ventures : smart clap lamp / Mohammad Iqbal Shauqi Hamdan...[et al.] - Hamdan, Mohammad Iqbal Shauqi; Isham, Muhammad Arif; Hafiz, Muhammad Hariz; Amir, Zul Fadzly; Azman, Siti Nur Aishah (2019)
Smart Clap Lamp will use pull strategy to make people aware of its products. It will be positioned as a product of moderate price and high quality. There will be various types of promotional campaign to make people aware of the product brand and amazing offers. The marketing tools will include TV Commercial and also posters. Smart Clap Lamp’s marketing budget is estimated in affordable method which will enable it to continue the huge sales promotion schedule. As Smart Clap Lamp is the new type of lamp product along with unique way to switch it on, that’s why there will be a great opportunity to grab the market share with higher demand. Smart Clap Lamp products will be produced in its own production in Pasir Gudang because of convenient transport and availability of raw materials. Finished product will be distributed with help of local distributor